The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.5005/jp-journals-10015-1651
|View full text |Cite
|
Sign up to set email alerts
|

Tasty Herb that Heals: A Review of Cosmos caudatus (Ulam Raja) and its Potential Uses in Dentistry

Abstract: Aim: In recent years, there has been an increase in research on herbal derivatives with regards to their medicinal use. This review aims to summarize the scientific reports on one such herb, Cosmos caudatus . Our primary focus is to highlight its pharmacological properties and their potential applications in the field of dentistry. Background: The vascular plant biodiversity of Southeast Asia is second to that of South America, with many of these plants being used for their traditional medicinal benefits. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…In Malaysia, there a few types of herbals that are commonly used to treat many kinds of diseases traditionally such as Ficus deltoidea , Labisia pumila , Cosmos caudatus and Nigella sativa ( Afzan et al 2019 ; Uzbek & Shahidan 2019 ; Mohamad et al 2019 ; Zakaria et al 2021 ). Among these herbals, Aquilaria species, locally known as Karas or Gaharu, is identified as one of the most valuable plants in Malaysia due to their high-value fragrant resinous wood (agarwood) ( Liu et al 2019 ; Desa et al 2021 ; Rozihawati et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, there a few types of herbals that are commonly used to treat many kinds of diseases traditionally such as Ficus deltoidea , Labisia pumila , Cosmos caudatus and Nigella sativa ( Afzan et al 2019 ; Uzbek & Shahidan 2019 ; Mohamad et al 2019 ; Zakaria et al 2021 ). Among these herbals, Aquilaria species, locally known as Karas or Gaharu, is identified as one of the most valuable plants in Malaysia due to their high-value fragrant resinous wood (agarwood) ( Liu et al 2019 ; Desa et al 2021 ; Rozihawati et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The leaves and shoots can be eaten raw as a side dish with meals as well as for other culinary purposes 2 , 3 . Previous work has been done on the plant extraction mostly on the leaves which reported various pharmacological properties such as anti-bacterial, anti-inflammatory, bone-protective agent, and anti-diabetic 2 , 4 – 9 . Some studies have demonstrated that the extract has more powerful antioxidant properties contrasted to some tropical fruits, herbs, and vegetables 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The plant extract from leaves possesses an excellent source of antioxidants and phenolic compounds as dominant compounds. Based on scientific evidence, the plant extract displays various pharmacological properties such as anti-bacterial, anti-inflammatory, bone-protective agent, and antidiabetic 1,[4][5][6] . Moreover, the extract of C. caudatus leaves has a strong antioxidant property and the content is higher compared to some tropical fruits, herbs, and vegetables 7,8 .…”
Section: Introductionmentioning
confidence: 99%